(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
In this paper, the Andelo’s mosaic inscription is analyzed from the perspective of the hypothesis raised by F. Beltrán based on the Latin inscription on pavement in La Cabañeta (El Burgo de Ebro), concluding that its consideration as ancient Basque testimony, defended by J. Velaza, allows its interpretation as a formula with a structure similar to that of the pavement with Iberian inscription of Caminreal.